2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591709
|View full text |Cite
|
Sign up to set email alerts
|

Localised impedance monitoring device for the remote clinical assessment of home-based dialysis patients

Abstract: BioImpedance Spectroscopy (BIS) has been clinically used to determine the hydrational status of patients undergoing haemodialysis (HD). In the present project we are developing a calf-localised, integrated impedimetric device to periodically and conveniently measure and transmit information on the hydrational status of home-based patients to a remote clinic. Surprisingly, we have found that simple postural changes before or during measurement lead to significant fluid shifts in the lower leg that are as import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Preliminary recordings have shown that the proposed solution is sensitive to dialysis-related changes in impedance for all body compartments. However, a significant influence of body position on the results of segmental BIA has been revealed, which may lead to measurement misinterpretation, for example, during classical hemodialysis [ 23 ]. Impedance at the electrode-skin interface plays a much more important role in segmental measurements than whole-body BIA measurement.…”
Section: Spectroscopy: Bioelectrical Impedance Analysismentioning
confidence: 99%
“…Preliminary recordings have shown that the proposed solution is sensitive to dialysis-related changes in impedance for all body compartments. However, a significant influence of body position on the results of segmental BIA has been revealed, which may lead to measurement misinterpretation, for example, during classical hemodialysis [ 23 ]. Impedance at the electrode-skin interface plays a much more important role in segmental measurements than whole-body BIA measurement.…”
Section: Spectroscopy: Bioelectrical Impedance Analysismentioning
confidence: 99%
“…[210]. However, this location may not be optimal for assessing the specific composition in a corporal segment, especially in those patients who suffer extreme changes in body composition, such as patients on hemodialysis or patients with spinal cord injury [367]. The measurement of segmental and localized bioimpedance is an area of study that requires additional research [210,367].…”
Section: Future Challenges Of Bioimpedancementioning
confidence: 99%